Korelasi Antara Lama Kebuntingan, Bobot Lahir dan Jenis Kelamin Pedet Hasil Inseminasi Buatan pada Sapi Bali - Prasojo, Gatot; Arifiantini, Iis; Mohamad, Kusdiantoro (Jurnal Veteriner; Vol 11 No 1 (2010), 2010)
Purpose of the research was to study the correlation between the gestation period with sex and birthweight of new born calves as the result of artificial insemination (AI) in bali cattle. Data were collecteddirectly from AI technicians in some districts in the province of bali from 1997 to 2003. A total, of 10759inseminated cows and 799 of which were with completed data of, date of birth, birth weight and sex ofcalves. The data were collected from 3 districts, involving Gianyar (205 samples), Badung (221 samples)and Bangli (373 samples). Result showed that the gestation period of bali cows were 284.4±5.7 days andbirth weight of 18.4±1.6 kg. Sex ratios (male : female) of bali calves resulted from AI in 1997 to 2003 were1.2:1. There were positive correlation between gestation period and birth weight (P>0.01) as well asbetween gestation period and sex of calves with a high correlation coefficient (0.075) which proved thatmale calves had longer gestation period than females.
Keywords: Gestation period, birth weight, seks ratio, bali cattle